Cotyledonoid Dissecting Leiomyoma with Symplastic Features: Case Report - Fatma Cavide Sonmez; Zeynep Tosuner; Ayse Filiz Gökmen Karasu; Dilek Sema Arıcı; Ramazan Dansuk (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Purpose Cotyledonoid dissecting leiomyoma is a leiomyoma variant exhibiting unusual growth patterns. We aimed to demonstrate this, as well as to point out another feature that has not been previously reported. Case Report A congested, multinodular myomectomy specimen was resected. Histologically, smoothmuscle fascicles with marked vascularity and extensive hydropic degeneration were detected. A total of 2 mitoses per 10 high power fields were counted, and the Ki-67 index was of 2-3%. We encountered atypical bizarre cells that have not been previously reported. Coagulative necrosis was not present. The patient was alive and well 36 months after surgery, with no evidence of recurrence. Conclusions Albeit the gross aggressive appearance, cotyledonoid dissecting leiomyomas are benign in nature. To this day, atypical cells have not been reported in this type of tumor. Despite the presence of symplastic features, cotyledonoid dissecting leiomyomas are clinically benign entities. Surgeons and pathologists should be acquainted with this variant.